2022
DOI: 10.1007/s10147-022-02167-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Idylla™ RAS-BRAF mutation test for formalin-fixed paraffin-embedded tissues of colorectal cancer

Abstract: Background The Biocartis Idylla™ platform is a fully automated, real-time PCR-based diagnostic system. The Idylla™KRAS and NRAS-BRAF Mutation Tests have been developed for the qualitative detection of mutations in KRAS, NRAS and BRAF genes, facilitating the genomic profiling of patients with colorectal cancer. The aim of the present study was to evaluate clinical performances of these tests in Japan. Methods The RAS and BRAF mutation statuses of 253 formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Other publications focused on FFPE sections have reported lower detection thresholds, ranging between 1% and 5% VAF [35][36][37], but with Cq ref values ranging from 20 to 23 [36]. Notably, larger multicenter studies have set input criteria of 10% [38], 20% [25], and even 30% [39] tumor content for Idylla. This variation may reflect differences in tumor content determination among pathologists, which becomes particularly relevant in cases of low cellularity and when studies are conducted prospectively across multiple centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other publications focused on FFPE sections have reported lower detection thresholds, ranging between 1% and 5% VAF [35][36][37], but with Cq ref values ranging from 20 to 23 [36]. Notably, larger multicenter studies have set input criteria of 10% [38], 20% [25], and even 30% [39] tumor content for Idylla. This variation may reflect differences in tumor content determination among pathologists, which becomes particularly relevant in cases of low cellularity and when studies are conducted prospectively across multiple centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, determining the sensitivity of del19 detection is touchier. We used 39 Regarding Idylla, 21 out of 31 (67.7%) del19 samples were correctly genotyped. Among the 10 misdetected del19 samples (samples 3, 4, 7, 8, 17, 51, 56, 67, 70, 71), two had Cq ref values > 26 (samples 51, 67) and were classified as FNq.…”
Section: Sensitivity and Adjusted Sensitivity-spectra Of Del19 Detectionmentioning
confidence: 99%
“…The colorectal team in our department also performed a comparison study between the Idylla assay and the MEBGEN RASKET-B assay for KRAS, NRAS, and BRAF mutations using 253 CRC specimens. The authors observed the potential clinical usefulness of the Idylla assay, showing a high concordance rate of 97.4%, a negative concordance rate of 95.7%, and overall concordance rate of 95.3% (κ = 0.919, 95% CI 0.871-0.967) [33]. Another group compared the Idylla assay with anti-BRAF V600E (clone VE1) immunohistochemistry in 90 melanoma samples.…”
Section: Discussionmentioning
confidence: 99%
“… OncoBEAM (Sysmex) CE-IVD KRAS & NRAS mCRC [ 75 ] 9. Idylla (Biocartis) CE-IVD KRAS NRAS, BRAF mCRC [ 76 ] 10. HCCBlood Test (Epigenomics AG) CE-IVD SEPT9 methylation HCC (patients with liver cirrhosis) [ 77 ] 11.…”
Section: Emerging Clinical Applications Of Liquid Biopsymentioning
confidence: 99%